Hope and Physical Exercise: The Contributions of Hope, Self-Efficacy, and Optimism in Accounting for Variance in Exercise Frequency. Issue 4 (August 2020) - Anderson, Craig L.; Feldman, David B.
We examine the relationship of hope with exercise using Snyder's hope model, which defines hope as a combination of goal-directed planning (pathways) and motivation (agency). We surveyed 102 participants online via Amazon MTurk. The Adult Hope Scale and Goal-Specific Hope Scale assessed general hope and hope regarding exercise. The Leisure-Time Exercise Questionnaire assessed frequency of exercise and of any activity "long enough to work up a sweat." We also measured optimism, exercise self-efficacy, depression, anxiety, and stress. Because hope emphasizes planning and motivation (both likely needed in fitness regimens), we expected it to relate to exercise frequency after controlling for these other variables. Indeed, exercise goal-specific hope was correlated with frequency of exercise and activity long enough to sweat, though general hope was not. This relationship held after controlling for all other variables. Future research may be useful in investigating causality, including whether hope-based interventions result in increased exercise engagement.